Effect of N-acetylcysteine administration on homocysteine level, oxidative damage to proteins, and levels of iron (Fe) and Fe-related proteins in lead-exposed workers. (September 2016) - Kasperczyk, Sławomir; Dobrakowski, Michał; Kasperczyk, Aleksandra; Romuk, Ewa; Rykaczewska-Czerwińska, Monika; Pawlas, Natalia; Birkner, Ewa
N -Acetylcysteine (NAC) could be included in protocols designed for the treatment of lead toxicity. Therefore, in this study, we decided to investigate the influence of NAC administration on homocysteine (Hcy) levels, oxidative damage to proteins, and the levels of iron (Fe), transferrin (TRF), and haptoglobin (HPG) in lead (Pb)-exposed workers. The examined population ( n = 171) was composed of male employees who worked with Pb. They were randomized into four groups. Workers who were not administered any antioxidants, drugs, vitamins, or dietary supplements were classified as the reference group ( n = 49). The remaining three groups consisted of workers who were treated orally with NAC at three different doses (1 × 200, 2 × 200, or 2 × 400 mg) for 12 weeks. After the treatment, blood Pb levels significantly decreased in the groups receiving NAC compared with the reference group. The protein concentration was not affected by NAC administration. In contrast, Hcy levels significantly decreased or showed a strong tendency toward lower values depending on the NAC dose. Levels of the protein carbonyl groups were significantly decreased in all of the groups receiving NAC. Conversely, glutamate dehydrogenase activity was significantly elevated in all of the groups receiving NAC, while the level of protein thiol groups was significantly elevated only in the group receiving 200 mg of NAC. Treatment with NAC did not significantly affect Fe and TRF levels, whereas HPG levels showed a tendency toward lower values. Treatment with NAC normalized the level of Hcy and decreased oxidative stress as measured by the protein carbonyl content; this effect occurred in a dose-dependent manner. Moreover, small doses of NAC elevated the levels of protein thiol groups. Therefore, NAC could be introduced as an alternative therapy for chronic Pb toxicity in humans.